Advancing Human Resource Practices In Hospitality: A Bibliometric Analysis Of Hris Adoption And Implications For Hr Professionals - Risna Amalia Ulfa; Kadek Wiweka; Lioe Lyly Soemarni; Sendy Fransiscus Tantono (STIE Pariwisata API Yogyakarta, 2025)
This bibliometric study investigates the evolution and scholarly trends surrounding the adoption of Human Resource Information Systems (HRIS) and their implications for human resource (HR) professionals within the hospitality sector. Employing a quantitative descriptive approach, the study assesses the global distribution and thematic focus of HRIS-related publications indexed in the Scopus database. The analysis reveals that 11 of the 40 reviewed articles affirm that the development and implementation of HRIS significantly enhance managerial efficiency by streamlining HR operations, optimising workforce utilisation, and reducing the demand for extensive HR investment. Furthermore, HRIS is recognised for fostering greater employee participation and contributing to organisational development. Recent literature offers valuable perspectives on the strategic integration of HRIS in the hospitality industry, particularly in addressing operational complexities such as shift scheduling, the management of seasonal labour, compliance with hospitality regulations, and the delivery of service excellence through targeted training. These insights are crucial in a sector characterised by high labour mobility, customer-centric performance standards, and operational unpredictability. This study contributes a comprehensive synthesis of the current knowledge landscape, identifying key research gaps and emerging directions. The findings reinforce the notion that HRIS is not only a tool for administrative efficiency but also a critical enabler of workforce engagement and performance optimisation in hotels and hospitality enterprises. The paper concludes with a call for future bibliometric and empirical research to bridge conceptual and practical dimensions of HRIS, especially concerning its integration with advanced technologies such as artificial intelligence (AI), blockchain, and 5G. These innovations are poised to reshape the contours of HR practice and digital transformation within the global hospitality industry.